Analisis Spasial Titik Rawan Kecelakaan Lalu Lintas (Blackspot) Di Kabupaten Banyuasin Menggunakan Kernel Density - Amaliasari, Fitri; Buchari, Erika; Kadarsa, Edi (Syntax Corporation, 2025)
The increase in population and mobility in Banyuasin Regency has a direct impact on traffic safety risks. Throughout 2023, 162 traffic accidents were recorded, exhibiting a fluctuating pattern. This study aims to identify and map the spatial distribution of accident-prone points (black spots) and measure the validity of the vulnerability model. The method employed is Geographic Information System (GIS)-based Kernel Density Estimation (KDE), utilizing 2023 incident data as the training set and January 2024 data for validation. The analysis integrates parameters of victim fatality, time of occurrence, and vehicle type. The results indicate the formation of a